A Genomic Reference Panel for Drosophila serrata - Reddiex, Adam J. (G3 (Bethesda), 2018)
Here we describe a collection of re-sequenced inbred lines of Drosophila serrata, sampled from a natural population situated deep within the species endemic distribution in Brisbane, Australia. D. serrata is a member of the speciose montium group whose members inhabit much of south east Asia and has been well studied for aspects of climatic adaptation, sexual selection, sexual dimorphism, and mate recognition. We sequenced 110 lines that were inbred via 17-20 generations of full-sib mating at an average coverage of 23.5x with paired-end Illumina reads. 15,228,692 biallelic SNPs passed quality control after being called using the Joint Genotyper for Inbred Lines (JGIL). Inbreeding was highly effective and the average levels of residual heterozygosity (0.86%) were well below theoretical expectations. As expected, linkage disequilibrium decayed rapidly, with r(2) dropping below 0.1 within 100 base pairs. With the exception of four closely related pairs of lines which may have been due to technical errors, there was no statistical support for population substructure. Consistent with other endemic populations of other Drosophila species, preliminary population genetic analyses revealed high nucleotide diversity and, on average, negative Tajima’s D values. A preliminary GWAS was performed on a cuticular hydrocarbon trait, 2-Me-C(28) revealing 4 SNPs passing Bonferroni significance residing in or near genes. One gene Cht9 may be involved in the transport of CHCs from the site of production (oenocytes) to the cuticle. Our panel will facilitate broader population genomic and quantitative genetic studies of this species and serve as an important complement to existing D. melanogaster panels that can be used to test for the conservation of genetic architectures across the Drosophila genus.